The Effect of Transformational Leadership, Organizational Commitment, Work Motivation, and Organizational Culture on Employee Performance in Indonesian Private Companies - Syaiful Amri; Sri Mulyani; Citra Astuti; Muhamamd Rizki Aulia Rizki Aulia (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Employee performance is a key determinant of organizational success in achieving its strategic goals. This study aims to analyze the influence of transformational leadership, organizational commitment, work motivation, and organizational culture on employee performance in private companies in Indonesia. Using a quantitative approach with a cross-sectional survey design, this study involved 320 employees from 18 private companies in Medan City, North Sumatra, selected through a proportionate stratified random sampling technique. Data were collected using a structured questionnaire with a 5-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 software. The results showed that transformational leadership had a positive and significant effect on employee performance (β = 0.312; p < 0.001), organizational commitment had a positive and significant effect (β = 0.274; p < 0.001), work motivation had a positive and significant effect (β = 0.198; p < 0.01), and organizational culture had a positive and significant effect (β = 0.167; p < 0.05) on employee performance. Simultaneously, the four independent variables explained 68.4% of the variance in employee performance (R² = 0.684). Transformational leadership proved to be the strongest predictor of employee performance. The findings of this study provide important implications for human resource management practices in Indonesian private companies, particularly in developing transformative leaders, strengthening employee commitment and motivation, and building an adaptive and high-achieving organizational culture.